2021
DOI: 10.1016/j.heliyon.2021.e06814
|View full text |Cite
|
Sign up to set email alerts
|

Action research improved general prerequisites for evidence-based practice

Abstract: The present study was part of an action research project that was performed to implement a clinical pathway for patients on mechanical ventilation and simultaneously explore the implementation process in a Swedish intensive care unit. The aim of this questionnaire study was to evaluate whether an action research methodology could affect the general prerequisites for evidence-based practice (EBP). Informed by the Promoting Action on Research Implementation in Health Services (PARIHS) framework, the study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…The rapid growth of cyberspace in the last two decades has given rise to the new phrase of cyber security, which is a sequel to information security or IT security ( Van den Berg, 2018). Based on a study by Bjurling-Sjöberg et al (2021), at baseline and followup, views on the recommendations were favorable and did not change significantly. Additionally, based on a study from Hagger et al (2020), in both populations, structural equation models revealed that habits at follow-up were consistent predictors of social distancing behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid growth of cyberspace in the last two decades has given rise to the new phrase of cyber security, which is a sequel to information security or IT security ( Van den Berg, 2018). Based on a study by Bjurling-Sjöberg et al (2021), at baseline and followup, views on the recommendations were favorable and did not change significantly. Additionally, based on a study from Hagger et al (2020), in both populations, structural equation models revealed that habits at follow-up were consistent predictors of social distancing behavior.…”
Section: Introductionmentioning
confidence: 99%